Double agents : queer citizenship(s) in contemporary South African visual culture - Stielau, Anna (Michaelis School of Fine Art, 2016)
South Africa claims the most progressive constitution on the African continent, extending protections to all citizens regardless of race, gender, ability or sexual orientation. Much has been published in recent years about the induction of LGBTIQ persons into this inclusive post-1994 human rights framework, often with a particular focus on the role of the state in instituting non-discrimination legislation and promoting equality. This document reflects my belief that South African sexuality scholarship too often presents incorporation into a unified nation-state as the only desirable outcome for queer citizens. By mapping the manner in which sexual difference has been uneasily imagined in national discourses, I argue here that the ideal South African citizen remains a heterosexual citizen presupposed as private, patriotic, familial and reproductive. I posit that when non-normative sexual identities and practices become visible in the public sphere, they risk assimilation into "acceptable" modes of representation produced in accordance with the expectations and responsibilities attending state-sanctioned national membership. In so doing, I assert, these cultural forms mandate a queerness that leaves structural inequalities intact. To look beyond this horizon I choose to explore dissident citizenship forms that intervene in dominant cultural narratives to expand the boundaries of belonging. Specifically, I concern myself with representations of queer subjects in visual culture and the multiple audiences these representations invite.